(untitled) (Carte Romanze, 2020)
This paper focuses on the life of the Galician-Portuguese poet known as Airas Paez, presenting a new interpretation of the lesser known sources and a transcription unpublished ones. The poet seems to have come from Navarre (although his family was probably Galician) and his activity, mainly in the service of James II of Aragon (with periods in other courts), spanned a longer period of time than is generally recognized. Finally, an edition of one of his cantigas d’amor, namely Dizen pela terra, senhor, ca vos amei, bears witness to a poet more talented than might appear from his (most well-known) cantigas d’amigo.